Exchange rates and global rebalancing - Barry Eichengreen; Gisela Rua (Asian Development Bank Institute (ADBI), 2011)
This paper considers the general equilibrium relationship between exchange rates and global imbalances. It emphasizes that the exchange rate is not a primitive but an equilibrium price determined by the policy mix. It uses extensions of the two-country Obstfeld-Rogoff model to analyze the response of imbalances and real exchange rates to shocks. Finally, it analyzes the characteristics of episodes in which chronic current account surpluses (as opposed to deficits) come to an end.
Keywords: F0; F3; F4; 330; Zahlungsbilanzungleichgewicht; Leistungsbilanz; Internationaler Finanzmarkt; Wechselkurs; Allgemeines Gleichgewicht; Zwei-Länder-Modell; Schätzung; Welt